Formulation and Cell Viability Assessment of Microparticles of Isolated Lactobacillus sp. with Alginate-Chitosan Solution (Jagannath University Journal of Life and Earth Sciences, 2024)
This study was performed to isolate the probiotic Lactobacillus sp. from dairy products available in Dhaka to form microparticles with isolated Lactobacillus probiotic bacteria and determine cell viability. Depending on their biological and physical traits and selective growth in MRS agar and MRS broth medium, the isolates were recognized as Lactobacillus spp. Major biochemical tests and growth at different temperatures were taken into account for the identification of the isolates. Low pH tolerance, homo- or hetero-fermentative activity, hydrolysis of arginine, and antibiotic susceptibility tests were conducted to assess probiotic activity. Among several isolates of Lactobacillus sp., four showed considerable tolerance to lower pH (pH 3.0) and growth at different temperatures (15 to 37°C). They were resistant to common antibiotics like penicillin (10µg), gentamicin (30µg), tetracycline (30µg), chloramphenicol (30µg), erythromycin (15µg) and streptomycin (30µg). The isolates were shown to have superior probiotic capabilities and may be employed as possible probiotic microorganisms after comparing all probiotic features evaluated in this experiment. The capacity of probiotic bacterial cells to survive when stored and in gastrointestinal transit is difficult to maintain. As a solution to these obstacles, microparticles were formulated with sodium alginate and chitosan. The cell viability check of the microparticles was continued for two weeks, and the response positively indicated increased stability. The results show promise for the encapsulation of the isolates.Jagannath University Journal of Life and Earth Sciences, 9(1): 69–80, 2023 (June)